2019
DOI: 10.30699/mmlj17.1.3.100
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mycoplasma Muris Isolated from Vaginal Samples of NIH Mice

Abstract: Mycoplasma murisPCR New strain 16S rRNA sequences NIH MiceMycoplasma muris (M.M) is a small pathogenic bacterium that lives in the female mouse genital tract. Mycoplasma muris may have harmful effects on the reproductive health of female. This research was performed to optimize the detection of M. muris in NIH mice in the Department of Animal Breeding, Razi Vaccine and Research Institute, Iran. In this cross-sectional study, 29 vaginal samples of NIH mice were selected through simple random sampling. For detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Also, M. collis was isolated for the first time from the conjunctiva and nasal cavity of mice and rats (HILL, 1983). M. muris, a scarce Mycoplasma type causing a huge hazardous effect on the reproductive efficiency of female mice, has been identified in recent years (Zinatizadeh et al, 2017). M. arthritidis, another rare pathogen of mice, is regarded as the main cause of arthritis in mice with swelling of legs and fingers (Constantopoulos and McGarrity, 1987).…”
Section: Laboratory Animals Laboratory Animals' Infectionmentioning
confidence: 99%
“…Also, M. collis was isolated for the first time from the conjunctiva and nasal cavity of mice and rats (HILL, 1983). M. muris, a scarce Mycoplasma type causing a huge hazardous effect on the reproductive efficiency of female mice, has been identified in recent years (Zinatizadeh et al, 2017). M. arthritidis, another rare pathogen of mice, is regarded as the main cause of arthritis in mice with swelling of legs and fingers (Constantopoulos and McGarrity, 1987).…”
Section: Laboratory Animals Laboratory Animals' Infectionmentioning
confidence: 99%
“…Mycoplasma muris, is a pathogenic bacterium in the mouse genital tract. 35 (It was observed that the rate of Mycoplasma muris (23,828%) increased significantly in rats treated with sinapic acid. The amount of Escherichia coli bacteria, the source of infection in the intestinal system, increased approximately two times in the group using ellagic acid compared to the control group.…”
Section: Discussionmentioning
confidence: 98%